CREDITING OF ENTERPRISE IN THE PERIOD OF FINANCIAL INSTABILITY ON WORLD MARKETS - D. E. Pucenich; Zh. G. Lutsaj; V. V. Akulova (Литьë и металлургия)
The sources of financing of RUP “BMZ” activity in the period of finance instability on the world markets are given